2017
DOI: 10.3390/molecules22091404
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lead on Generation of Signalling Molecules and Accumulation of Flavonoids in Pea Seedlings in Response to Pea Aphid Infestation

Abstract: The aim of this study was to investigate the effect of an abiotic factor, i.e., lead at various concentrations (low causing a hormesis effect and causing high toxicity effects), on the generation of signalling molecules in pea (Pisum sativum L. cv. Cysterski) seedlings and then during infestation by the pea aphid (Acyrthosiphon pisum Harris). The second objective was to verify whether the presence of lead in pea seedling organs and induction of signalling pathways dependent on the concentration of this metal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 168 publications
0
25
1
Order By: Relevance
“…To some extent it also explains the recently postulated phenomenon of a dose-dependent response to HMs, called hormesis. According to this concept, metallic elements with unknown physiological function may have a beneficial impact on organisms when they are applied in low concentration, which has been observed not only for the tested CAL ecotype of S. vulgaris, but also for species such as Brassica napus treated with Cd ions [5] or Pisum sativum under Pb exposition [4]. Therefore, the applied HMs doses, which induced various disturbances in other ecotypes, did not exceed the toxic thresholds for the CAL one and may be considered as trace elements for proper growth and development.…”
Section: Morphogenetic Response Of Hm-treated Cultures Is Diversifiedmentioning
confidence: 99%
See 1 more Smart Citation
“…To some extent it also explains the recently postulated phenomenon of a dose-dependent response to HMs, called hormesis. According to this concept, metallic elements with unknown physiological function may have a beneficial impact on organisms when they are applied in low concentration, which has been observed not only for the tested CAL ecotype of S. vulgaris, but also for species such as Brassica napus treated with Cd ions [5] or Pisum sativum under Pb exposition [4]. Therefore, the applied HMs doses, which induced various disturbances in other ecotypes, did not exceed the toxic thresholds for the CAL one and may be considered as trace elements for proper growth and development.…”
Section: Morphogenetic Response Of Hm-treated Cultures Is Diversifiedmentioning
confidence: 99%
“…Some HMs, such as zinc (Zn), nickel (Ni), or copper (Cu), are fundamental to different physiological processes and required in trace amounts for higher plants [2]. Others, like lead (Pb) and cadmium (Cd), do not have recognized beneficial roles, although more and more research has recently indicated their positive effects on morpho-physiological traits under low-dose treatment [3][4][5][6]. Despite their biological necessity, HMs…”
Section: Introductionmentioning
confidence: 99%
“…Feeding by stylet may avoid aphid ingestion of potentially toxic phenolic from the phloem. Although numerous studies show that the aphid infection can induce flavonoid synthesis and accumulation in plants, and some flavonoids possess inhibitory effects on aphid growth and reproduction rate, details about the location of toxic compounds have not previously been determined (Smith and Chuang, 2014;Morkunas et al, 2016;Woźniak et al, 2017). Flavonoids are likely synthesized in a cytoplasmic metabolic environment, and the flavonoid biosynthetic genes are regulated by light, but the long distance movement of flavonoids is largely unknown (Buer et al, 2007).…”
Section: Secondary Metabolites Play a Complex Role In Plantinvader Inmentioning
confidence: 99%
“…This pattern resembles the concept of hormesis often deployed by toxicologists to describe the response to toxins, where exposure to a low dose is beneficial while a higher dose results toxicity due to overcompensation in response to disruption of homeostasis 53 . While tissue-specific hormetic responses have been described in flies, where a virus-acquired cytokine relays ageing 54 , and examples of abiotic factors or signalling molecules affecting peas and aphid infestation 55 , immunity in plants 56,57 , life-span in malaria-transmitting Anopheles 58 , and larval development in Black Cutworm 59 , this example here could be the first involving a eukaryotic host-pathogen relationship. The underlying factor remains to be elucidated but C. neoformans ’ highly immunogenic capsule seems to be an excellent candidate 48 .…”
Section: Discussionmentioning
confidence: 91%